"The Prefatory/Postscript Letters to St. Thomas More’s Utopia: The Culture of ‘Seeing’ as a Reality-Conferring Strategy" (Journal of Early Modern Studies, 2014)
The article discusses the significance of on-the-spot observation and eye witnessing as powerful scientific tools for establishing the real in the early sixteenth century. In particular, I argue that the simulation of such tools in the paratextual material to Utopia, especially the prefatory/postscript letters, enhance, preemptively, the verisimilitude of the Utopian society as well as the materiality of the island at hand. If eye witnessing is reality-conferring, then, the powerful Renaissance act of reading a text as a simulation of eye witnessing is reality-conferring too. In this light, to read Utopia through the paratextual letters is to place one’s trust in the literal existence of Utopia insofar as reading simulates the act of seeing with one’s own eyes and bearing witness to a palpable reality. Keywords: Eye Witnessing, Humanism, Paratext, Utopia, Verisimilitude 1. Paratext, Utopia and Liminality Nearly five hundred years after its first publication in 1516, Thomas More’s Utopia continues to spark endless discussions in relation to its potential meanings or its exact nature.1 More could not have written Utopia at a better time. As Alistair Fox maintains, when he sat down to write it in 1515, ‘His imagination had been excited by the discoveries of Cabot and Vespucci in the New World… the momentum of Erasmian reform was approaching its height; and he had the stimulating company… of Cuthbert Tunstal, Busleyden and Peter Giles, humanists with interests and ambitions similar to his own’ (1984, 53). The publication of Utopia was accompanied by paratextual material (at times called parerga) – maps, illustrations, verses as well as a number of letters written by friends or acquaintances from the wider humanist continental circles. By fervently supporting the project, this paratextual material – which was altered to a great degree from edition to edition, thus also constantly reshaping readers’ reception of Utopia – worked towards legitimising More’s endeavour, establishing its truthfulness, and announcing beforehand its acceptance by early sixteenth-century readership.2 ‘Paratext’ in literature covers everything that lies around a text. Gérard Genette has famously called paratext ‘a zone between text and off-text, a zone not only of transition but also of transaction’ between the author(s) and the public, or ‘the most socialized side of the practice of literature’ (1997, 1, 14).